[Web resistance] a study of Filipino music video parodies on youtube - Pamatmat, Glenn Kevin M. 1989-; Canlas, Daphne T. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2011)
"As a reader, I analyzed the local Youtube music video parodies as new media texts by addressing the theoretical inquiry: How is the new media used to challenge the dominant ideology of colonial mentality? I studied how resistance was perpetuated in the local music video parodies of Lady Gagita and Moymoypalaboy through the costumes, props, set/venue, technical aspect and actors. Moreover, I wanted to determine the themes covered through the analysis of these indicators of resistance in the videos. This paper focused on the Filipino web video parodies on the online video uploading and sharing site, Youtube. This research used the framework of cultural hegemony of Antonio Gramsci to understand the interplay of some content in new media to oppose the dominant ideology. The study found that there are certain forms of resistance against colonial mentality present in different texts in the videos such as the use of the popularity of the original songs, costumes, props, set or venue, the technical aspect and even the actors in the videos. Consequently, the resistance formed in these texts coherently highlighted themes such as the videos' ongoing resistance against foreign enculturation, ideologic replacement, familiarity and locality, creativity and artistry, participation in the cultural aspect of globalization and 'filipinizing' the colonial texts."
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman